The Quality of Alkali Treated Cottonii (ATC) Made from Eucheuma cottonii Collected from Different Regions In Indonesia - darmawan, muhamad; Bandol Utomo, Bagus Sediadi; Yuda Mulia, Raekal Amral (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2013)
The presented study has been carried out in order to study the quality of Alkali Treated Cottonii (ATC) made from Eucheuma cottonii which being collected from different regions in Indonesia (Belitung, Nusa Tenggara Barat and Lampung). The quality variables analyzed were the characteristics of raw materials (Clean anhydrous weed and impurities) and the characteristics of ATC produced (moisture content, ash content, acid insoluble ash content, yield, gel strength, sulphate content, gelling -melting point). The analysis was done in 3 replicates and the data were statistically analyzed using SPSS 15 package software. Results indicated that the raw material from Lampung had a better quality than those from Nusa Tenggara Barat and Belitung. In addition, the characteristics of ATC produced from these three raw materials showed that seaweed from Lampung produced better quality ATC than those from Nusa Tenggara Barat and Belitung in terms of their gel strength, sulphate content and yield.